Could antioxidants play a role in high rates of coronary heart disease in the Czech Republic? - Bobák, M; Brunner, E; Miller, N J; Skodová, Z; Marmot, M (European journal of clinical nutrition, 1998)
OBJECTIVES: To compare plasma levels of antioxidant vitamins in the Czech population with those in a western European population, and to investigate whether plasma levels of antioxidant vitamins in Czech population are related to risk of MI. DESIGN: The study has two parts: a cross-sectional survey and a population based case-control study. SETTING: Adult population in two districts of the Czech Republic, and London based civil servants group as the comparison. SUBJECTS: A random sample of men and women aged 25-64y resident in two districts were selected for the cross- sectional survey. Subjects in the age group 40-49 y were compared to a sample of British civil servants of the same age enrolled in the Whitehall II Study. Men in the Czech sample served as controls to 52 male cases of first non-fatal myocardial infarction (MI) which occurred in the same population. Plasma samples were obtained from venepuncture during an interview in hospital in the population sample and immediately after hospitalization in the MI cases. MAIN OUTCOME MEASURES: Plasma levels of beta-carotene and alpha-tocopherol, and the event of MI. Identical protocol and one laboratory was used for all analyses. RESULTS: The mean plasma levels of beta-carotene and alpha-tocopherol in healthy Czech men and women were substantially lower than in a subsample of British civil servants examined in the same laboratory. Smoking was strongly related to beta-carotene in both populations but differences between Czechs and Brits were present in both smokers and non-smokers. In the case-control study among Czech men, low levels of the vitamins were strongly related to an increases risk of MI. Age-adjusted odds ratios for concentrations below the median were 3.33 (95% confidence interval 1.43-8.33) for beta-carotene and 1.89 (0.94-3.45) for alpha-tocopherol; further adjustment for a range of variables reduced these estimates only slightly. CONCLUSIONS: Plasma concentrations of antioxidants in the Czech population appeared to be very low, and men with low levels of these substances are at increased risk of MI. This indicates that sub-optimal intake of antioxidants or related dietary factors may have played a role in the high rates of coronary heart disease in this population.
Keywords: Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; Vitamin E; Multivariate Analysis; Female; dospělí; Spojené království; lidé; Antioxidants; United Kingdom; beta Carotene; antioxidancia; beta-karoten; Adult; ženské pohlaví; multivariační analýza; Male; Middle Aged; koronární nemoc; Coronary Disease; Czech Republic; Cross-Sectional Studies; Smoking; Česká republika; mužské pohlaví; kouření; vitamin E; průřezové studie